Global Analysis of Gene Expression in Response to Whole-Chromosome Aneuploidy in Hexaploid Wheat. Issue 2 (18th August 2017) - Zhang, Ai; Li, Ning; Gong, Lei; Gou, Xiaowan; Wang, Bin; Deng, Xin; Li, Changping; Dong, Qianli; Zhang, Huakun; Liu, Bao
Abstract : Aneuploidy in hexaploid wheat induces dysregulated gene expression due to the combined action of dosage effect, dosage compensation, and transcriptional response, which brings about diverse phenotypes. Abstract: Aneuploidy, a condition of unbalanced chromosome content, represents a large-effect mutation that bears significant relevance to human health and microbe adaptation. As such, extensive studies of aneuploidy have been conducted in unicellular model organisms and cancer cells. Aneuploidy also frequently is associated with plant polyploidization, but its impact on gene expression and its relevance to polyploid genome evolution/functional innovation remain largely unknown. Here, we used a panel of diverse types of whole-chromosome aneuploidy of hexaploid wheat ( Triticum aestivum ), all under the common genetic background of cv Chinese Spring, to systemically investigate the impact of aneuploidy on genome-, subgenome-, and chromosome-wide gene expression. Compared with prior findings in haploid or diploid aneuploid systems, we unravel additional and novel features of alteration in global gene expression resulting from the two major impacts of aneuploidy, cis- and trans-regulation, as well as dosage compensation. We show that the expression-altered genes map evenly along each chromosome, with no evidence for coregulating aggregated expression domains. However, chromosomes and subgenomes in hexaploid wheat are unequal in their responses to aneuploidy with respect to the number of genes being dysregulated. Strikingly, homeologous chromosomes do not differ from nonhomologous chromosomes in terms of aneuploidy-induced trans-acting effects, suggesting that the three constituent subgenomes of hexaploid wheat are largely uncoupled at the transcriptional level of gene regulation. Together, our findings shed new insights into the functional interplay between homeologous chromosomes and interactions between subgenomes in hexaploid wheat, which bear implications to further our understanding of allopolyploid genome evolution and efforts in breeding new allopolyploid crops.